2016
DOI: 10.7860/jcdr/2016/19487.8597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citalopram in Combination with Omega-3 on Depression in Post- menopausal Women: A Triple Blind Randomized Controlled Trial

Abstract: Using omega-3, can reduce the severity of depression in post-menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Finally, we found only one RCT study exploring the combined effect of n-3 LCPUFAs and SSRI (citalopram) for the treatment of 60 postmenopausal depressed women (aged 45–65 years old) [ 74 ]. This is a triple-blind randomized controlled trial where the control group received 20 mg citalopram plus a placebo, whereas the intervention group received 20 mg citalopram and 1 g of n-3 LCPUFAs for a week.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we found only one RCT study exploring the combined effect of n-3 LCPUFAs and SSRI (citalopram) for the treatment of 60 postmenopausal depressed women (aged 45–65 years old) [ 74 ]. This is a triple-blind randomized controlled trial where the control group received 20 mg citalopram plus a placebo, whereas the intervention group received 20 mg citalopram and 1 g of n-3 LCPUFAs for a week.…”
Section: Resultsmentioning
confidence: 99%
“…The same authors [51] reported that a diet with high n-6:n-3 PUFA ratios is associated in the elderly with an elevated risk of depression and inflammatory diseases. Only trends regarding to depression could be seen in 60 females aged 45-65 in a triple blind design study of PUFA supplementation in combination with citalopram [52]. A placebo-controlled study on shift workers (n = 136) demonstrated reduced BDI scores in all groups, including placebo [53,54].…”
Section: Other Supplementsmentioning
confidence: 99%
“…As a natural source of PUFA, fish oil, combined with a Mediterranean diet, also had a positive effect on depression [60]. Administration of supplements like DHA, PUFA, and fish oil showed a positive effect therapeutical approach, inflammatory factors, pathophysiology, and pathoetiology of depression [49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Other Supplementsmentioning
confidence: 99%
“…In cognitive behavioral approach, attention is paid to sex education that Iranian couples need and do not obtain by a reliable method. [27,28] According to the mentioned issues, it is determined that, in the culture of Iranian society, paying attention to cognitive factors is highly important to resolve sexual problems, dysfunction, and dissatisfaction and neglecting them leads to a decrease in therapeutic purposes. Cognitive-behavioral family therapy training causes the couples to be equipped with skills necessary for marital life and generalizes these teachings to other levels of marital and social levels of life.…”
Section: Discussionmentioning
confidence: 99%